Inovasi Pelatihan Kepenulisan Karya Ilmiah Berbasis Artificial intelegence dalam Meningkatkan Budaya Akademik di Perguruan Tinggi Keislaman - Yogi Sopian Haris; Wantini; Muh. Zulkifli; Rizky Hanifah; Lalu Wire Sanni Atmaja; Raychan Assabiq; Windila Santoso (Advances In Education Journal, 2025)
The main issue in the development of an academic culture, particularly in writing at Islamic higher education institutions including IAIH NW Lombok Timur, is the low level of digital literacy and the lack of innovation in scientific writing. Students struggle to write independently and ethically, while the use of AI has not yet been accompanied by adequate critical understanding and academic ethics. This research aims to analyze the impact of AI-based scientific writing training in shaping an excellent academic culture, as well as to formulate strategies and ethics for its utilization in line with Islamic values. The method used is quantitative through post-test questionnaires and documentation, with descriptive statistical analysis. The results show that the use of AI such as ChatGPT and Grammarly improves the quality, productivity, and acceleration of writing, but digital literacy, AI usage guidelines, and ethical awareness still need to be strengthened. This research also recommends an integrative scheme that combines technical strategies, faculty mentoring, and the internalization of Islamic values so that AI functions as an intellectual partner, not a substitute for students' scientific reasoning.